2008
DOI: 10.2165/00129784-200808020-00001
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy of a Combination of Niacin Extended Release and Simvastatin in Patients with Dyslipidemia

Abstract: Treatment with NER/S 2,000/40 mg/day is well tolerated, has no unanticipated adverse events, and provides additional, clinically relevant improvements in multiple lipid parameters beyond statin monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 24 publications
2
63
0
3
Order By: Relevance
“…In the OCEANS study, 68% of patients using an 8-week extended-release niacin and simvastatin titration schedule experienced flushing compared with approximately 74% of those using a 12-week titration. 57 Regimens of patients receiving the PGD 2 antagonist laropiprant along with extended-release niacin have consisted of a 2-step schedule: initiating niacin treatment at the relatively high daily dose of 1.0 g, which was maintained for 4 weeks, and then escalating to 2 g at treatment week 4 and maintaining this dose for 12 weeks. 142 In my practice, we use a combination of these 2 approaches, starting low (0.5 g/d) and going slowly (for a total of 8 weeks) until a stable dose of 1.0 g has been reached.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the OCEANS study, 68% of patients using an 8-week extended-release niacin and simvastatin titration schedule experienced flushing compared with approximately 74% of those using a 12-week titration. 57 Regimens of patients receiving the PGD 2 antagonist laropiprant along with extended-release niacin have consisted of a 2-step schedule: initiating niacin treatment at the relatively high daily dose of 1.0 g, which was maintained for 4 weeks, and then escalating to 2 g at treatment week 4 and maintaining this dose for 12 weeks. 142 In my practice, we use a combination of these 2 approaches, starting low (0.5 g/d) and going slowly (for a total of 8 weeks) until a stable dose of 1.0 g has been reached.…”
Section: Discussionmentioning
confidence: 99%
“…tients discontinued treatment because of flushing. [54][55][56][57][58][59][60] The long-term OCEANS (Open-Label Evaluation of the Safety and Efficacy of a Combination of Niacin Extended-Release and Simvastatin in Patients with Dyslipidemia) study showed that less than 40% of patients who experienced flushing in the first 12 weeks of treatment, when extended-release niacin/simvastatin doses were being escalated from 0.5 g/40 mg to 2.0 g/40 mg, did so during the following 12 weeks. 57 In the SEACOAST (Safety and Efficacy of a Combination of Niacin ER and Simvastatin in Patients With Dyslipidemia) trial, 27% of patients who experienced flushing while taking 1.0 g/20 mg of extended-release niacin/simvastatin (and 30% of patients taking 2.0 g/20 mg of extendedrelease niacin/simvastatin) during the first 12 weeks but who completed the study did not flush during the second 12 weeks.…”
Section: Frequencies Of Flushing and Related Discontinuations With Nimentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed the superior efficacy of combining extended release niacin and simvastatin (3)(4). However, the rate of niacin discontinuation due to flushing is over 80% even with extended release niacin (32), and increases over the course of treatment (33)(34); moreover, the flush can not be reduced by ASA (325 mg/day), ibuprofen (200 mg/day) or selective PGD 2 receptor antagonists by more than 30% (11)(12)35).…”
Section: Discussionmentioning
confidence: 99%
“…The randomized, 52-week OCEANS (Open-Label Evaluation of the Safety and Efficacy of a Combination of Niacin ER and Simvastatin in Patients with Dyslipidaemia) study [17] randomized patients to 8-or 12-week niacin ER/simvastatin titration schedules (maximum daily dosage 2000 mg/40 mg). Patients were withdrawn from the study if they did not reach LDL-C NCEP ATP III goals at 24 weeks.…”
Section: Is Longer-term Treatment Effective?mentioning
confidence: 99%